China’s Arctic Policy - Koivurova, Timo; Kopra, Sanna; Lanteigne, Marc; Nojonen, Matti; Śmieszek, Małgorzata (Gosia); Stępień, Adam (Brill Nijhoff, 2020)
This chapter elaborates on China’s evolving strategy in the Arctic. For China, the Arctic is no longer about simply being an observer in the Arctic Council, but much more. The chapter will analyze mainly the specifics of China’s Arctic white paper and examine a pair of specific cases, namely China’s role in negotiating the Polar Code and the Arctic fisheries agreement. Special attention will be paid to the ways in which China’s national policy towards the Arctic has emerged and how it has been viewed by other actors and commentators following China’s role in the Arctic. As a sub-section, China’s policy towards the Arctic’s indigenous peoples will also be studied.